Characterization of failure in integrated circuit due to electrostatic discharge (ESD) - Goh, Jia Jun. (2010)
Electrostatic discharge (ESD) is the momentary electric current that flows between two objects of different electrical potentials. It is the result of static charge build-up on at least one of the objects, and this charge is often sufficiently large enough to cause catastrophic or latent defect failures to integrated circuits in the semiconductor industry. Despite advancements in ESD protection, ESD still affects production yields, manufacturing costs, product quality, reliability and profitability. In addition, as a result of electronic devices becoming faster and smaller in scale, their sensitivity to ESD has actually increased.